A Fast Detection Method via Region‐Based Fully Convolutional Neural Networks for Shield Tunnel Lining Defects. (23rd April 2018) - Xue, Yadong; Li, Yicheng
Abstract: Tunnel lining defects are an important indicator reflecting the safety status of shield tunnels. Inspired by the state‐of‐the‐art deep learning, a method for automatic intelligent classification and detection methodology of tunnel lining defects is presented. A fully convolutional network (FCN) model for classification is proposed. Information about defects, collected using charge‐coupled device cameras, was used to train the model. The model's performance was compared to those of GoogLeNet and VGG. The best‐set accuracy of the proposed model was over 95% at a test‐time speed of 48 ms per image. For defects detection, image features were computed from large‐scale images by the FCN and then detected using a region proposal network and position‐sensitive region of interest pooling. Some indices (detection rate, detection accuracy, and detection efficiency, locating accuracy) were used to evaluate the model. The comparisons with faster R‐CNN and a traditional method were conducted. The results show that the model is very fast and efficient, allowing automatic intelligent classification and detection of tunnel lining defects.